(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The Spanish Education Workers’ Federation (Federación de Trabajadores de la Enseñanza, fete) included mainly teachers following the socialist ideology, although a significant group of its members were communist teachers and professors, as well as some left-wing republicans. It played a fundamental role all through the five-year long republican rule and during the Civil War and it became the main, almost predominant, trade union in education in Spain —with the exception of the anarchists, who kept their own minority trade union. As soon as the military conflict was over (but also in the course of it), the pro-Franco repression targeted fete activists. Nevertheless, a large number of their leaders and most active members managed to leave Spain for France. Very soon, the majority of them continued their way to Mexico, where they reorganized the trade union. The present paper analyzes this reconstruction process, as well as the educational and cultural activities developed by fete in Mexico between 1939 and 1949. Finally, in 1949, the leaders of the trade union moved back to France, which at the same time led to the disappearance of the Mexican organization.